Ectomycorrhizas and tipping points in forest ecosystems - Suz, Laura M.; Bidartondo, Martin I.; van der Linde, Sietse; Kuyper, Thomas W. (The New phytologist, 2021)
The resilience of forests is compromised by human-induced environmental influences pushing them towards tipping points and resulting in major shifts in ecosystem state that might be difficult to reverse, are difficult to predict and manage, and can have vast ecological, economic and social consequences. The literature on tipping points has grown rapidly, but almost exclusively based on aquatic and aboveground systems. So far little effort has been made to make links to soil systems, where change is not as drastically apparent, timescales may differ and recovery may be slower. Predicting belowground ecosystem state transitions and recovery, and their impacts on aboveground systems, remains a major scientific, practical and policy challenge. Recently observed major changes in aboveground tree condition across European forests are probably causally linked to ectomycorrhizal (EM) fungal changes belowground. Based on recent breakthroughs in data collection and analysis, we apply tipping point theory to forests, including their belowground component, focusing on EM fungi; link environmental thresholds for EM fungi with nutrient imbalances in forest trees; explore the role of phenotypic plasticity in EM fungal adaptation to, and recovery from, environmental change; and propose major positive feedback mechanisms to understand, address and predict forest ecosystem tipping points.